A cobertura do desastre socioambiental em Mariana/MG pelo portal em.com.br: das fontes aos enunciadores - Souza, Elise Azambuja (2019)
The object of study of the present paper was the coverage by the portal em.com.br from Minas Gerais of the disaster caused by the collapse of the tailings dam operated by the mining company Samarco in the town of Mariana on 5 November 2015. Based on the understanding of the public character of journalism and its responsibility to provide coverages that address the plurality of versions, we adopted the Polyphonic Theory of Enunciation (DUCROT, 1987), which proposes the difference between speakers and enunciators as distinct utterance instances, as the main theoretical-methodological reference for understanding the viewpoints taken by the chosen sources. We analysed four phases of the coverage from within the period known in the press as "Rota da Lama". In support of this perspective, we subscribed to the event approach (QUÉRÉ, 2005) in order to envision the disputes located around the disaster in question and the different problematic fields on which light is shed after its irruption. In parallel to the ritual strategies of objectivity (TUCHMAN, 2016), we concluded that the use of sources in the coverage happens as a strategic ritual of polyphony, and the viewpoints mobilised by the sources evince different problematic fields of the event, which are the real orchestrators of the discourses about it.